Achillessehne - Weisskopf, L.; Segesser, B. (Sport-Orthopädie - Sport-Traumatologie, 2011)
Achilles tendon pathologies are difficult to treat and are connected with the need of long term therapy protocols. There is no evidence that corticosteroids have a positive therapeutic effect for any Achilles tendon disorders but they are still used because of beneficial short term effects, despite their high potential of complications. Corticosteroids have a negative impact on tenocytes and their collagen synthesis. As a consequence there is an increased risk of tendon rupture for many weeks after the injection and even after surgical repair the rate of re-rupture are significantly higher than non-cortisone patients. Damage of the soft tissue around the tendon especially the skin and atrophy of the subcutaneous tissue increases the rate of skin breakdown and postoperative infections. The localisation of the injection (peritendinous or intratendinous) and type of corticosteroids is from our point of view not of primary relevance for potential complications. Corticosteroid therapy for Achilles tendon disorders should be avoided completely (short time gain for long time pain!)